Evaluation of lens distortion errors in video-based motion analysis - Poliner, J.; Wilmington, R.; Klute, G. K.; Miocchi, A. (Technical paper 3266, 1993)
Video based motion analysis systems are widely used to study human movement. These systems use computers to aid in the capturing, storing, processing, and analyzing of video data. One of the errors inherent in such systems is that caused by distortions introduced by the camera and lens. Wide-angle lenses are often used in environments where there is little room to position cameras to record an activity of interest. Wide-angle lenses distort images in a somewhat predictable manner. Even "standard" lenses tend to have some degree of distortion associated with them. These lens distortions will introduce errors into any analysis performed with video-based motion analysis systems.